How Can Local Government Sustain a Terminated National Development Project? An Exit Strategy for the Techno Park Project in Tasikmalaya Regency, West Java, Indonesia - Satya Laksana; Fityan Aonillah; Rubi Azhara (The Journal of Indonesia Sustainable Development Planning, 2020)
The sixth of nine Indonesian national development agendas under the President Joko Widodo administration is to increase productivity and competitiveness, one of which is by the establishment of Techno Parks. The projects will be terminated in 2019; however, exit strategies that contribute to sustainable development have been rarely considered throughout the history of development studies and practice. This paper examines the concept of exit strategies within the context of a case study of the Indonesian Institute of Sciences (LIPI)-assisted project of the Tasikmalaya Techno Park (TP) from 2015-2019. It addresses two questions: (1) How has LIPI executed the TP project in Tasikmalaya throughout the period? (2) What is the recommended exit strategy for regional policymakers after project termination? To overview the implementation of TP activities, an internal- external analysis was conducted, and to formulate exit strategies, SWOT and QSPM were employed. Data were collected from July-September 2018, consisting of primary data collected from competent respondents by semi-structured and in-depth interviews selected by the purposive sampling method as well as secondary data compiled from relevant institutions. The conclusion is that the Tasikmalaya TP has five core businesses and its mission is to become a center for dissemination, technology transfer, and agribusiness incubator. The TP was present in quadrant I, meaning that aggressive strategies were recommended. There were four future management options and independent management was considered as the most appropriate. Its role should be more supported by middle- to long-term strategies and a well prepared legal system. Policy implications are discussed.